Summary of Expert Opinion on the Management of Children With Chronic Kidney Disease and Growth Failure With Human Growth Hormone - Cappa, Marco; Maghnie, Mohamad; Carbone, Vincenza; Chioma, Laura; Errichiello, Carmela; Giavoli, Claudia; Giordano, Mario; Guazzarotti, Laura; Klain, Antonella; Montini, Giovanni; Murer, Luisa; Parpagnoli, Maria; et al. (Frontiers in Endocrinology, 2020)
Background: The management of children and adolescents with chronic kidney disease (CKD) and growth failure candidate for recombinant human growth hormone therapy (rhGH) is based on an appraisal of the literature established on a 2006 consensus statement and 2019 Clinical practice recommendations. The performance of these guidelines has never been tested. Aims: The objective of this study was to establish the level of adherence to international guidelines based on the 2006 consensus and the 2019 criteria that lead to the initiation of growth hormone treatment by both pediatric endocrinologists and pediatric nephrologists. Methods: A multidisciplinary team of pediatric endocrinologists and pediatric nephrologists, members of the Italian Society of Pediatric Endocrinology or of the Italian Society of Pediatric Nephrology, discussed and reviewed the main issues related to the management of pediatric patients with CKD who need treatment with rhGH. Experts developed eleven questions focusing on risk assessment and decision makings in October 2019 and a survey was sent to forty pediatric endocrinologists (n = 20) and nephrologists (n = 20) covering the whole national territory. The results were then analyzed and discussed in light of current clinical practice guidelines and recent recommendations. Results: Responses were received from 32 of the 40 invited specialists, 17 of whom were pediatric endocrinologists (42.5%) and 15 pediatric nephrologists (37.5%). Although all the centers that participated in the survey agreed to follow the clinical and biochemical diagnostic work-up and the criteria for the treatment of patients with CKD, among the Italian centers there was a wide variety of decision-making processes. Conclusions: Despite current guidelines for the management of children with CKD and growth failure, its use varies widely between centers and rhGH is prescribed in a relatively small number of patients and rarely after kidney transplantation. Several raised issues are not taken into account by international guidelines and a multidisciplinary approach with mutual collaboration between specialists will improve patient care based on their unmet needs.